География сабақтарында проблемалық оқыту əдістерін қолдану - Баймаганбетова, К.Т.; Ахметова, Э.Б. (My University, 2016)
It is very important to have a teaching method in order to utilize new technologies correctly and efficiently. Therefore, taking into account this necessities, topicality of the article was dedicated to preparation and efficient implication of methodology of technology of problematic teaching in geography lessons. The aim of the article is to construct the methodology of technology of problematic teaching and presenting the ways of its implication in geography classes. Methods of the research: grouping, systemizing and analyzing. This article argues one of the methods of contemporary technologies, problematic teaching,its description, advantages and disadvantages. In addition, the article illustrates technics of implication of problematic teaching in geography lessons.
Keywords: problematic teaching; training; method case-study; problem; discussion